VO2 kinetics determined by PRBS techniques differentiate elite endurance runners from elite sprinters - Edwards, A. M.; Challis, N. V.; Chapman, J. H.; Claxton, D. B.; Fysh, M. L. (International Journal of Sports Medicine, 1999)
The aim of the study was to examine whether a measure of oxygen uptake (VO2) kinetics could differentiate between 12 elite male endurance (3000-10,000 m) runners and 12 elite male sprint (100-400 m) runners using a pseudo random binary sequence (PRBS) exercise protocol. All exercise tests were performed on an electrically braked cycle ergometer at a constant pedal frequency of 1 Hz. The PRBS exercise intensities alternated between 25 W and 85 W for three consecutive PRBS cycles of 300 s. VO2 was measured breath-by-breath and results were analysed by Fourier techniques in the frequency domain. Blood lactate concentrations taken pre and post testing were below 2 mM. Significantly greater amplitude components were observed in the endurance runners than sprinters at frequencies 6.7 mHz (6.71 +/- 1.09 and 5.47 +/- 0.95 ml x min(-1) x W(-1), respectively) P<0.05 and 10 mHz (4.97 +/- 0.98 and 3.56 +/- 0.69 ml x min(-1) x W(-1) respectively) P<0.01. Phase shift components were significantly shorter in the endurance runners compared to the sprinters at frequency 3.3 mHz (-35.45 +/- 4.31 and -41.26 +/- 5.82 degrees respectively) P<0.05. The results of this study show that VO2 kinetics are differentially faster in elite endurance runners than in elite sprinters. This supports the development of the PRBS technique as a test of sports performance.